2021
DOI: 10.3390/ijms221910559
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and COVID-19: An Overview of Recent Evidence

Abstract: The novel coronavirus severe acute respiratory syndrome (SARS-CoV-2) has progressed rapidly from an outbreak to a global pandemic, with new variants rapidly emerging. Coronavirus disease 2019 (COVID-19), the disease resulting from SARS-CoV-2 infection, can lead to multiorgan damage. Due to the extremely contagious and fatal nature of the virus, it has been a priority of medical research to find effective means of treatment. Amid this search, the role of vitamin D in modulating various aspects of the innate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 168 publications
2
30
0
9
Order By: Relevance
“…In addition, low levels of Vitamin D are associated with Se deficiency and are related to COVID-19 severity, old age, obesity, diabetes and dyslipidemia. However, in COVID-19 patients without comorbidities, there is also a decrease in Vitamin D and Se in comparison with the healthy subjects [68]. The participation of Se is also important in COVID-19 because it has synergic effects with Vitamin D and E acting as antioxidants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, low levels of Vitamin D are associated with Se deficiency and are related to COVID-19 severity, old age, obesity, diabetes and dyslipidemia. However, in COVID-19 patients without comorbidities, there is also a decrease in Vitamin D and Se in comparison with the healthy subjects [68]. The participation of Se is also important in COVID-19 because it has synergic effects with Vitamin D and E acting as antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, levels of Vitamin D are low in diseases that course with hyperinsulinemia such as COVID-19 and in the pathologies that comprise the MS [67,68]. Vitamin D exerts its effects by binding to a nuclear Vitamin D receptor, which is expressed in various immune cells, with particularly high levels in dendritic cells, macrophages, T and B lymphocytes that are increased when the innate immune response is elicited [69].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in that study vitamin D treatment started around the 11th day of symptoms. Thus, we cannot exclude that the treatment has been started too late for vitamin D to be effective (after patients have developed severe COVID-19), since the primary effects of vitamin D on SARS-CoV-2 infection are to reduce the viability of the virus through inducing cathelicidin and reducing the risk of the cytokine and chemokine storm ( 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GERIA-COVID trial, which focused on elderly patients, tested vitamin D supplementation before or during disease and reported that the 3-month death rate of patients was reduced and survival length was prolonged [ 32 ]. Overall, it is currently believed that an adequate supply of vitamin D during the current pandemic will support the immune system and improve overall survival in COVID-19, while vitamin D deficiency would be an unnecessary and avoidable risk factor [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%